2022
DOI: 10.3390/healthcare10112276
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Meaning from Chaos: The Mediating Role of the Sense of Coherence in the Serial Relationships among Fear of COVID-19, Indices of Psychological Distress, and Life Satisfaction

Abstract: The current study focused on the role of the sense of coherence (SOC) in the serial relationships among the fear of COVID-19, indices of psychological distress, and life satisfaction. It examined the hypothesis that an SOC would mitigate the impact of the fear of COVID-19 on psychological distress, which in turn would positively impact life satisfaction. Participants were school teachers (N = 355) who completed the Fear of COVID-19 Scale, the trait scale of the State-Trait Anxiety Inventory, the Beck Hopelessn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Existing studies have identified fortitude, ego-resilience, a sense of coherence, and social support as protective factors or resilience resources in the context of the COVID-19 pandemic (Grey et al, 2020; Padmanabhanunni & Pretorius, 2021a, 2021b; Pretorius & Padmanabhanunni, 2022a; van der Velden et al, 2020). The current study aimed to extend this work by investigating whether adaptive cognitive appraisals – specifically appraisals of problem-solving ability and appraisals of support received from others – serve as protective resources for mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have identified fortitude, ego-resilience, a sense of coherence, and social support as protective factors or resilience resources in the context of the COVID-19 pandemic (Grey et al, 2020; Padmanabhanunni & Pretorius, 2021a, 2021b; Pretorius & Padmanabhanunni, 2022a; van der Velden et al, 2020). The current study aimed to extend this work by investigating whether adaptive cognitive appraisals – specifically appraisals of problem-solving ability and appraisals of support received from others – serve as protective resources for mental health.…”
Section: Introductionmentioning
confidence: 99%